Managing Toe Walking, a Treatment Side Effect, in a Child With T-Cell Non-Hodgkin's Lymphoma: A Case Report - Kiebzak, Wojciech; Żurawski, Arkadiusz; Zmyślna, Anna; Pogorzelska, Justyna; Domagalska-Szopa, Małgorzata; Hagner-Derengowska, Magdalena; Szopa, Andrzej (Frontiers in Pediatrics, 2019)
Background and Purpose. Children who have survived cancer are at risk of experiencing adverse effects of the cancer or its treatments. One of the adverse effects may be the limitation of ankle dorsiflexion (DF), which may result in 'toe walking'. Although there is an increasing number of studies in pediatric oncology presenting evidences of different therapeutic interventions to improve DF function, none of these therapeutic interventions has been sufficiently documented. This case report shows the results of non-invasive neurodevelopmental treatment program combined with application of inhibiting casts in a pediatric cancer patient who presented with severe and persistent toe walking. The treatment was aimed to improve DF function, postural and gait pattern and to normalize weight distribution between forefoot and heel. Case Presentation. A 7-year-old girl with T-cell lymphoma, who presented with severe and persistent toe walking, was assessed 10 times over a course of six months by both clinical examination (ankle range of motion measurement) and neurophysiological measures (weight distribution between forefoot and hindfoot, postural sway, body posture, and gait). Outcomes. Neurodevelopmental treatment program combined with application of inhibiting casts for three months increased passive ankle DF by 10° in both lower limbs, normalized weight distribution between the forefoot and heel in both lower limbs, as well as established a heel-toe walking gait pattern. Improved ankle DF function, and normalized postural and gait patterns were maintained in repeated examinations even three months after the removal inhibiting casts. Discussion. Early identification of toe walking in the female pediatric patient with T-cell non-Hodgkin lymphoma and early physiotherapy intervention were beneficial in terms of her body posture and gait pattern development. Non-invasive neurodevelopmental treatment program combined with application of inhibiting casts as described in this study can be useful for managing treatment side effects in pediatric cancer patients.